Development and application of global assays of hyper‐ and hypofibrinolysis. Issue 1 (6th November 2019) - Ilich, Anton; Noubouossie, Denis F.; Henderson, Michael; Ellsworth, Patrick; Molitor, Kathleen F.; Campello, Elena; Meeks, Shannon; Dunn, Amy; Park, Myung S.; Pawlinski, Rafal; Simioni, Paolo; Shapiro, Amy; et al.
Abstract: Numerous methods for evaluation of global fibrinolytic activity in whole blood or plasma have been proposed, with the majority based on tissue‐type plasminogen activator (t‐PA) addition to initiate fibrinolysis. We propose that such an approach is useful to reveal hypofibrinolysis, but t‐PA concentrations should be kept to a minimum. In this paper, we describe a low‐concentration t‐PA plasma turbidity assay to evaluate several congenital factor deficiencies, including plasminogen activator inhibitor‐1 (PAI‐1) and plasminogen deficiency, as well as hemophilia A and B. In addition, we demonstrate a threshold dependency on endogenous PAI‐1 levels. To assess endogenous hyperfibrinolysis, we suggest that assays that avoid t‐PA addition are preferable, with assays based on euglobulin fractionation remaining a viable choice. We describe a euglobulin fraction clot lysis time (ECLT) assay with spectrophotometric readout and other modifications, and evaluate it as a tool to measure hyperfibrinolysis in inherited clotting factor deficiency states. We demonstrate that the ECLT is predominantly driven by residual amounts of PAI‐1, t‐PA, and α2 ‐antiplasmin. These assays should be further evaluated for the detection of hypo‐ or hyperfibrinolysis in acquired thrombotic or hemorrhagic disorders.